2000
DOI: 10.1006/mthe.2000.0207
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorochemical Liquid Enhances Adeno-Associated Virus-Mediated Transgene Expression in Lungs

Abstract: Use of adeno-associated virus (AAV) vectors for lung gene therapy is limited, in part, by low levels of AAV-mediated transgene expression in lungs. Generally, less than 1% of total airway and alveolar epithelial cells express transgene activity following vector administration. A means of improving AAV vector delivery could potentially enhance AAV-mediated gene expression in lungs. We have previously demonstrated that use of perfluorochemical (PFC) liquids improved overall levels of adenovirus vector-mediated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…A significant number of preclinical animal studies have been performed with various serotypes of rAAV delivered to the lung. In rodent animal models, rAAV vectors delivered to the lung have shown promising results (47)(48)(49)(50). Such encouraging results have also been confirmed in larger animal models such as rabbit, sheep, and nonhuman primate (51)(52)(53).…”
Section: Recombinant Adeno-associated Virusmentioning
confidence: 87%
“…A significant number of preclinical animal studies have been performed with various serotypes of rAAV delivered to the lung. In rodent animal models, rAAV vectors delivered to the lung have shown promising results (47)(48)(49)(50). Such encouraging results have also been confirmed in larger animal models such as rabbit, sheep, and nonhuman primate (51)(52)(53).…”
Section: Recombinant Adeno-associated Virusmentioning
confidence: 87%
“…In situ alkaline phosphatase activity was detected in mounted cryosections of macaque lungs incubated overnight with 2-dicyclohexylphosphino-2¢,4¢,6¢-triisopropylbiphenyl (XPhos) and nitroblue tetrazolium, using standard techniques (Weiss et al, 2000).…”
Section: Detection Of Alkaline Phosphatase Activitymentioning
confidence: 99%
“…Importantly, PFC has also been shown to enhance gene transfer in abnormal lungs (Weiss et al, 1999b) suggesting that it may be efficacious in the CF lung. PFC also enhances AAV vector mediated gene delivery [Weiss et al, 2000] and has been shown to be effective in enhancing adenoviral mediated gene delivery to primate lung airways [Weiss et al, 2002a]. PFCs appear to enhance gene delivery by both facilitating vector dispersion and propulsion through the airway, and by transiently permeabilising tight junctions .…”
Section: Disruption Of Airway Barriers To Vector Transduction and Othmentioning
confidence: 99%
“…AAV-6 has been shown to efficiently transduce murine airways and to transduce airway epithelial cells more efficiently than AAV-2, a significant advantage for CF gene therapy [Halbert et al, 2001]. AAV-6 also appears to be less immunogenic than AAV-2 in mice Various agents have been shown to enhance airway gene delivery with different AAV vector serotypes including gelling agents (AAV-5) [Sinn et al, 2005], PFC (AAV-2) [Weiss et al, 2000] and proteasome inhibitors (AAV-2) (see previous section for details).…”
Section: Adeno-associated Virus Vectorsmentioning
confidence: 99%